A dual‐center evaluation of platelet culture vials to detect the presence of microorganisms in platelets. Issue 1 (25th November 2019) - Denys, Gerald; Tulpule, Anagha; Roth, Jessica; Warns, Patty; Collins, Tiffany; Mindel, Susan
Abstract : BACKGROUND: Microorganism contamination of platelets results in a high risk of transfusion‐related sepsis. Here, the ability of culture vials (BD BACTEC Platelet Aerobic/F and Platelet Anaerobic/F vials, Becton, Dickinson and Company) to detect microorganisms in leukoreduced apheresis platelets (LRAPs) and leukoreduced whole blood platelet concentrates (LRWBPCs) was assessed. METHODS: LRAPs or LRWBPCs were inoculated into Aerobic/F and Anaerobic/F vials and placed in a blood culturing system (BD BACTEC FX System, Becton, Dickinson and Company) for growth/monitoring over 7 days to detect preexisting contamination during false‐positive testing. Subsequently, platelets were seeded with microorganisms at approximately 10 CFU/mL or approximately 1 CFU/mL to simulate contamination. Aerobic/F and Anaerobic/F vials were inoculated with platelets (sets of 12). Microorganism growth was detected in the BACTEC FX instrument over 7 days. Overall, 2925 vials were tested. RESULTS: Of the 1905 vials included in the microorganism detection phase, 63 (3.3%) Aerobic/F and 16 (0.8%) Anaerobic/F vials were both BACTEC FX and subculture negative. From the remaining 1827 vials, two (0.1%) Anaerobic/F vials were false positive; no false positives were observed in Aerobic/F vials, and no false negatives occurred in either vial type. Of the remaining 1825 vials (99.9%), 955 Aerobic/F and 870 Anaerobic/F vials were true positives. The mean‐time‐to‐detection range was 8.5 to 77 hours. All true‐positive Aerobic/F and Anaerobic/F vials showed 100% agreement with subculture for positive identification of seeded microorganisms. CONCLUSION: Aerobic/F and Anaerobic/F vials facilitate contamination detection in LRAPs and LRWBPCs down to approximately 1 CFU/mL. These results support the use of Aerobic/F and Anaerobic/F vials for quality control testing of platelets before transfusion.